2020
DOI: 10.1186/s12957-020-02005-4
|View full text |Cite
|
Sign up to set email alerts
|

Results following surgical resection of recurrent chordoma of the spine: experience in a single institution

Abstract: Background: Chordoma of the spine is a low-grade malignant tumor with vague and indolent symptoms; thus, large tumor mass is encountered at the time of diagnosis in almost cases and makes it difficult for en-bloc freemargin resection. Salvage therapy for recurrent chordoma is very challenging due to its relentless nature and refractory to adjuvant therapies. The aim of this present study was to report the oncologic outcome following surgical resection of chordoma of the spine. Materials and methods: Retrospect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…For chordomas, wide en-bloc resection is not always possible, either because of the size or extent of the tumor or because such resection would lead to excessive morbidity ( 25 ).The limitation of this paper is that we did not provide accurate information about postoperative margins, because only 10 patients in our study reported clear postoperative negative margins (R0 margins), and none of the rest recorded margins. This may affect the accuracy of prognosis.…”
Section: Discussionmentioning
confidence: 90%
“…For chordomas, wide en-bloc resection is not always possible, either because of the size or extent of the tumor or because such resection would lead to excessive morbidity ( 25 ).The limitation of this paper is that we did not provide accurate information about postoperative margins, because only 10 patients in our study reported clear postoperative negative margins (R0 margins), and none of the rest recorded margins. This may affect the accuracy of prognosis.…”
Section: Discussionmentioning
confidence: 90%
“…History of radiation therapy, dedifferentiated histological subtype, and the presence of metastasis were associated with poorer survival, and patients with pre-recurrence radiotherapy had the longest time to recurrence and mortality. 20 logical outcome following the resection of spinal chordomas. 20 Their findings showed that en bloc free-margin resection is preventive of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…20 logical outcome following the resection of spinal chordomas. 20 Their findings showed that en bloc free-margin resection is preventive of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Given the relative scarcity of these tumors, most of the previous literature has combined primary and recurrent chordomas into a single cohort and included chordomas in all locations. 3,517 These studies demonstrated poor overall local recurrence-free survival and overall survival, but en bloc and gross total excision tend to improve survival rates. 3,4,6,17,18…”
mentioning
confidence: 99%
“…3,517 These studies demonstrated poor overall local recurrence-free survival and overall survival, but en bloc and gross total excision tend to improve survival rates. 3,4,6,17,18…”
mentioning
confidence: 99%